Η ζωή στη σχολική τάξη: Σύνδεσμοι μεταξύ υποστήριξης, συνεργασίας και σχολικής αυτοεκτίμησης - Θ Μπαμπάλης; Γαλανάκη, Ε.; Ν Σταύρου (Επιστήμες Αγωγής, 2007)
The aim of this research study was to examine the associations between teacher and student academic and personal support, cooperation, and academic self-esteem during late childhood. Participants were 221 fifth- and sixth-grade children from Athens. They completed six subscales of the Classroom Life Measure (Johnson, Johnson, Buckman, & Richards, 1985). Results showed the expected positive links among all the above variables. Correlations varied as a function of the source and type of support. When low/high cooperation and low/high academic self-esteem groups were distinguished, the associations proved to be robust. Age differences were not found, but correlations were significantly higher for girls than for boys. Results are discussed in the framework of the existing literature on the links among these facets of classroom life, and some suggestions for educational practice are made.